Antimicrobial, Antioxidant, Cytotoxicity and DNA Protective Properties of the Pink Oyster Mushroom, Pleurotus djamor (Agaricomycetes) - Inci, Sule; Akyuz, Mehmet; Kirbag, Sevda (Begell House Inc, 2023)
In this study, pink oyster mushroom Pleurotus djamor was cultivated using wheat straw (WS), quinoa stalk (QS), and their mixtures (WS-QS (1:1)) as substrate and evaluated in terms of antimicrobial, antioxidant, cytotoxicity, and DNA protective effects. Gram-positive and Gram-negative pathogen bacteria (Bacillus subtilis, Proteus vulgaris, Streptococcus mutans, Salmonella typhi, Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli), dermatophyte (Trichophyton sp.) and yeast (Candida tropicalis) were used in the study. It was found to be very active against all bacteria (except S. mutans and S. typhi), and dermatophyte when compared to the control groups (8.7-33.3 mm), but low against C. tropicalis. It was seen that the best total antioxidant assay (TAS) value was 2.05 mmol/L on WS-QS (1:1). Depend on, it was determined that the total oxidant assay (TOS) value (5.26 mu mol/L) in the same compost was lower than the others, and also the scavenging effect of 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) was higher on WS at 25 mg/mL (84.20%). The methanol extract on WS at a concentration of 400 mu g/mL, significantly reduced the percentage of viability in the human breast cancer (MDA-MB-231) cell line (2.2%). The methanol extracts on WS and QS medium were found to inhibit DNA damage induced by UV radiation and H2O2 at a concentration of 25 mg/mL. These results showed that pink oyster mushroom has benefits such as antimicrobial, antioxidant, cytotoxic, and DNA protective effects.
Keywords: Pleurotus djamor; pink oyster mushroom; antimicrobial; antioxidant; cytotoxic; DNA protective effect; medicinal mushrooms